The repercussions of social shocks on the social structure in the city of Fallujah - Fahd, Saleh Hadi; Hassan, Nabil Noman Ismail (Al-Adab Journal, 2021)
Since the beginning of the eighties of the last century, Iraq has lived long and continuous years of crises when it fought in the midst of two wars and an economic blockade since August 1990 and then the occupation of Iraq in 2003. All these developments left dangerous effects and repercussions on the societal conditions of Iraq in terms of material and human and caused a crack in its construction, balance and functions. On another level, these circumstances have caused pollution in the psychological and social climate on the ground, which has become saturated with the dust of enmity and hostility among its children. There is the fact that the effects of war on society and the consequent problems in the moral and ethical aspects and the public relations of society is the most influential and complex problem of the post-war in particular. It remains tilted to such an extent that it is difficult to predict its effects in a society like Iraqi society.